Thermomonospora spp. are implicated in the biodegradation of long-chain aliphatic polyester bioplastics during thermophilic composting - Lerner, Harry; Eck, Marcel; Link, Christoph; Witt, Timo; Battagliarin, Glauco; Mecking, Stefan; Schleheck, David (Frontiers in Microbiology, 2025)
Biodegradable plastics are an important component for achieving a circular polymer economy. To be considered biodegradable at the regulatory level, plastics must pass standardized tests, for example under industrial composting conditions at 58 °C (ISO 14855-1). Although such tests are frequently applied, little is known about the microorganisms catalyzing these degradation processes. Recently, bioplastics with properties similar to polyethylene, Long-Chain Aliphatic Polyesters (LCAP), for example polyester 1,18-octadecanediol-alt-1,18-octadecanedioic acid (abbreviated PE-18,18), were shown to biodegrade under industrial composting conditions. In this work, we analyzed the microbial communities that had developed in the compost treatments at the end of the biodegradation test for three different LCAPs (PE-18,18, PE-12,12 and PE-2,18) relative to the untreated controls, via amplicon-sequencing of bacterial 16S and fungal ITS2 rDNA. This revealed significant treatment-induced shifts in the bacterial communities (p < 0.05), with Pseudonocardia and Thermomonospora ASVs enriched in all LCAP-treated samples compared to the controls (p ≤ 0.0001), while no pronounced shifts were observed for the fungal community. Thermomonospora sequences showed high similarity to T. curvata DSM43183, which encodes the known polyester hydrolase Tcur1278, and the presence of gene tcur1278 was confirmed in LCAP-treated samples via PCR. Enzyme assays with heterologously expressed and partially purified Tcur1278 demonstrated its activity on PE-2,18 LCAP, releasing up to 230 μmol of soluble monomers over 48 h at 50 °C. Hence, our study implicated Thermomonospora species in LCAP degradation during thermophilic composting, based on taxonomic enrichment, and provided evidence linking the detected phylotypes to Tcur1278, the first bacterial enzyme demonstrated to depolymerize LCAP. It thereby is the first evidence for an ecological relevance of Tcur1278-encoding Thermomonospora phylotypes for bioplastic degradation in situ.